Industrial internet of things in the food industry - Rosell, Erik; Sai, Aron (My University, 2019)
When technological change affects an industry, incumbent firms sometimes fail and give way to new entrants, and sometimes they thrive. Ex post studies suggest factors inside and outside the firms that have influenced the outcome of such technological changes. This thesis aims to review these factors. The factors are then applied to a change where the outcome is not yet clear. The chosen change is the Industrial Internet of Things (IIoT) entering the food industry. The aim is to enable firms in the food industry to assess their readiness for the change. An extensive literature review compiles five factors that could determine an incumbent’s readiness for technological change. The factors are the incumbent’s existing competences and strategic beliefs, the type of innovation, the incumbent’s incentives to invest, its complementary assets, and its relationships in its value chain. This set of factors is then related to incumbents in the food industry in the case of a technological change due to IIoT, using supporting interviews with experts for further context. For each of the factors, a set of assessments is proposed for firms in the industry so they can understand their relative readiness ahead of the change. The five factors could each affect the food industry in nuanced ways during a transition due to IIoT. Firstly, investing in IIoT competences is required for incumbent firms, while it is possible to enhance the expertise within food production. If the industry shifts towards mass customization, new architectural knowledge might be needed, harming incumbents. The firms’ lack of willingness to invest is deemed a significant challenge for them, opening for new entrants to win market share. Most existing systems are considered complementary assets, potentially protecting firms while they adapt. Finally, firms might need to switch suppliers while maintaining their strong relationships with customers and consumers in order to perform well during the transition. Since not all factors align in terms of advantage or disadvantage for incumbent firms, no prediction is made regarding the outcome of this technological change. However, the framework could provide nuanced guidance for firms when preparing for this change. By collecting more data from the industry, the framework could be extended further, for example by including additional complementary assets. Future research into mass customization, consumer transparency, and the effect of regulations could provide additional context for the framework. Finally, the set of factors identified in the literature review along with the general manner of analysis provide research progress as they could be applied to other industries and technologies.
Keywords: technological change and industrial transformation; Industrial Internet of Things; food industry; production systems